Impact of natural aerosols on atmospheric radiation and consequent feedbacks with the meteorological and photochemical state of the atmosphere. Issue 3 (7th February 2014) - Kushta, J.; Kallos, G.; Astitha, M.; Solomos, S.; Spyrou, C.; Mitsakou, C.; Lelieveld, J.
Abstract This paper addresses the aerosol effects on radiation and the feedback on meteorology and photochemical activity, applying the online model RAMS/ICLAMS. The model treats meteorology and chemical pollutants on an interactive way. Cloud condensation nuclei (CCN), giant cloud condensation nuclei, and ice nuclei are treated as predictive quantities. The calculation of the aerosol optical properties accounts for size‐resolved mineral dust and size‐ and humidity‐dependent optical properties of sea salt. The simulations with and without aerosol impacts reveal the complex direct and indirect mechanisms through which the alteration of radiation fluxes influences meteorology and photochemical processes. For the specific dust event, the reduction in the surface shortwave radiation over cloudless regions affected by dust averages at ~ −75 W m−2 at 12:00 UTC per unit dust loading (1 g m−2). The increase on downwelling longwave radiation over the same areas and time averages at ~ 40 W m−2 per unit dust loading (1 g m−2). Surface upwelling longwave radiation over Mediterranean exhibits a complex daytime behavior. During midnight, the inclusion of dust leads to larger upwelling longwave radiation fluxes over the African continent. The net downward longwave radiation over cloudless areas exhibits an increase both during noon and midnight with the inclusion of dust. The results show that the vertical structure of the dust layer governs the magnitude of the feedback on radiation. The activation of natural particles as CCN causes small changes in radiation fluxes and temperature. Precipitation is influenced more by the indirect rather than the direct and semidirect effects.